Training loads during the marathon preparatory phase - a case study of the Polish marathon record holder - Szost, S.; Ozimek, M.; Mirek, W.; Ciepielowska, J. (Journal of Kinesiology and Exercise Sciences, 2018)
Introduction. For many years researchers and coaches have been struggling with a crucial experimental problem of examining the relations between sport result and the elements of training loads. The main question of the theory of endurance sports is the study of the influence of varied activities on human system, which will eventually transfer into results improvement. By enriching the scientific knowledge regarding organism adaptation to different stimuli in terms of physiology, biochemistry, biomechanics and physical therapy, coaches and scholars have been developing theoretical foundations of workout. Purpose of research. The main purpose of this study is to analyse the training loads of the competitive marathoner, the polish marathon record holder. The analysis is based on two mesocycles with a duration of 8 weeks of preparatory phase, guided by two different coaches. Moreover, another crucial issue included in the study is the comparison of the training framework and training loads in particular weeks. Material and method. The practical implementation of the theory is provided with the use of research material of Olympian, who is also the Polish marathon record holder, in a form of his workout logs. The content of the workout logs includes two marathon mesocycles, each with a duration of 8 weeks of preparatory phase. Results. The analysis of the volume of training loads in the eight-week mesocycle shows the diversity between the two studied marathon preparatory phases. Considering the efficacy based on the race result, it should be said that the workout plan of the first coach came out to be more beneficial for the marathoner. Conclusions. Hence, it should be said that it is the general running endurance which should be the main workout element of every elite runner. Increased number of kilometers definitely conduces to achieve satisfactory marathon results. Moreover, one should remember that most of the marathon work should be done in oxygen balance. Key words: marathon, training loads, runner, preparatory phase